2016
DOI: 10.1017/s0022215116009312
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of tonsillectomies: relationship with surgical technique, post-operative pain and haemorrhage

Abstract: Cold dissection produces less tissue damage, which is associated with lower incidence of complications. This study suggests that cold dissection is the technique of choice for tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Cold dissection technique causes less tissue damage compared to electrocautery [ 23 ], and convincing evidence suggests that TE performed with cold dissection techniques is superior to hot techniques in terms of postoperative late bleeding and pain [ 24 31 ]. The large sample size in the present study supports this by demonstrating longer time on analgesics and higher frequency of contacts with health care services in children operated with hot dissection technique.…”
Section: Discussionmentioning
confidence: 99%
“…Cold dissection technique causes less tissue damage compared to electrocautery [ 23 ], and convincing evidence suggests that TE performed with cold dissection techniques is superior to hot techniques in terms of postoperative late bleeding and pain [ 24 31 ]. The large sample size in the present study supports this by demonstrating longer time on analgesics and higher frequency of contacts with health care services in children operated with hot dissection technique.…”
Section: Discussionmentioning
confidence: 99%
“…10 necessary to determine the optimum surgical technique. Magdalena et al [5] have compared histological findings for tonsils removed by cold or electrocautery dissection and their relationship with post-operative complications. They found that patients in the cold dissection group experienced less pain ( p == 0.001) and fewer secondary haemorrhage episodes.…”
Section: Cold Dissectionmentioning
confidence: 99%
“…It is generally accepted that primary PTH is due to inadequate hemostasis and secondary PTH is related to tissue trauma incurred during dissection and hemostasis 1,7,8 . A wide body of literature reports the lowest secondary bleeding rates are associated with purely cold (no diathermy) techniques 8–16 . These are considered the “gold standard.” 17 Unfortunately purely cold techniques lead to higher intraoperative blood loss 6,17 and rates of primary PTH, 11,12,18,19 which is difficult to rationalize especially for a young child 4,6,10,14,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These are considered the “gold standard.” 17 Unfortunately purely cold techniques lead to higher intraoperative blood loss 6,17 and rates of primary PTH, 11,12,18,19 which is difficult to rationalize especially for a young child 4,6,10,14,20 . In contradistinction, techniques utilizing diathermy (hot) components for either dissection or hemostasis have been shown to result in higher rates of secondary PTH 8–11,16,19 …”
Section: Introductionmentioning
confidence: 99%